Evaluation of mobility parameters in individuals with Parkinson's disease with and without freezing of gait - Morais, Cristiane Ramos de; Capato, Tamine T. C.; Cabral, Ariana Moura; Andrade, Adriano de Oliveira (Arquivos de Neuro-Psiquiatria, 2025)
Background Individuals with Parkinson's disease (PD) often experience gait disturbances, and one of the most disabling is freezing of gait (FOG), which is characterized by the inability to initiate or continue walking. To identify its impact on the mobility of PD patients, it is necessary to objectively assess mobility and conduct systematic gait evaluations.Objective To evaluate mobility and gait parameters in individuals with PD with and without FOG.Methods The present cross-sectional study included a group of individuals with PD, divided into those with and without FOG, and a healthy control group. The Timed Up and Go (TUG) test was used to evaluate gait and mobility of the participants. Activities of daily living and motor performance in PD patients were assessed through parts II and III of the Movement Disorder Society Unified Parkinson Disease Rating Scale (MDS-UPDRS), while FOG was assessed through the New Freezing of Gait Questionnaire (NFOG-Q).Results A significant difference between the case and control groups was observed in the mean time it took to perform the TUG test, regardless of FOG, during the off-medication state. Unlike the group without FOG, there was a difference in the time it took to perform the tests between medication states in the group with FOG. Additionally, a correlation was found between TUG time and MDS-UPDRS scores in the FOG group.Conclusion Mobility in PD is influenced by medication effect and the presence of FOG. The results highlight the importance of objective and systematic gait evaluations to identify mobility problems, develop effective rehabilitation strategies, and optimize pharmacological treatments, especially for individuals with FOG.
Keywords: Parkinson Disease; Gait; Freezing; Rehabilitation; Mobility Limitation